Relaciones intrafamiliares y episodios depresivos en una estudiante de la carrera de Física de la Universidad Yachay Tech - Mera Barriga, Bryan Mauricio (2022)
The present case study aims to determine the incidence of intrafamilial relations in depressive episodes in a student of the Physics degree of Yachay Tech University, in which purposes were raised such as conceptualizing about intrafamilial relations and depressive episodes through bibliographic compilation of authors who carried out studies on the topics, a second objective was to determine the quality of intrafamilial relations and the mood in the patient by means of various information-gathering instruments, Finally, the aim was to establish results based on the theoretical and methodological sections on the incidence of the variables. This research is correlative, not experimental and has a mixed approach. As far as the instruments were applied mainly the Family Climate Scale (FES) and the Beck Depression Inventory (BDI) for the evaluation of a 21-year-old university student from the city of Quevedo. The results found that the patient has a mean trend in the FES and obtained a score of 39 points in BDI, finally it could be concluded that if there is a relationship between conflicting intrafamilial relations and the major depressive disorder of the patient.